Characteristics of the Electrocardiogram in Japanese Fabry Patients Under Long-Term Enzyme Replacement Therapy - Morimoto, Satoshi; Nojiri, Ayumi; Fukuro, Eiko; Anan, Ikuko; Kawai, Makoto; Sakurai, Ken; Kobayashi, Masahisa; Kobayashi, Hiroshi; Ida, Hiroyuki; Ohashi, Toya; Shibata, Takahiro; Yoshimura, Michihiro; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objective: An electrocardiogram (ECG) is an important tool for demonstrating cardiac manifestations in various heart diseases. The present study clarified the characteristics of ECG parameters in Japanese Fabry patients under long-term enzyme replacement therapy (ERT). Methods: We analyzed the ECGs of 40 Fabry patients (male, n=17; female, n=23) before and after treatment with ERT. To evaluate the atrio-ventricular conduction, the PQ interval, corrected PQ and PQ minus P-wave in lead II (Pend-Q) were calculated. The QRS duration, QTc, Sokolow-Lyon index and strain pattern were also examined. Results: At the baseline, the shortening of the PQ interval, corrected PQ and Pend-Q was identified in 7.5%, 25.0% and 47.5% of cases, respectively. The prolongation of QRS duration and QTc was found in 7.5% and 40.0% of cases, respectively. The strain pattern was mainly identified in female patients, irrespective of left ventricular hypertrophy (LVH). During long-term ERT, the PQ interval, corrected PQ and Pend-Q did not change significantly. The QRS duration was significantly prolonged in both genders, whereas the QTc was significantly prolonged only in male patients. A subgroup analysis revealed that the prolongation of the QRS duration and QTc only occurred in male patients with LVH and only occurred in female patients with the classical type mutation. The prevalence of the strain was significantly increased only in male patients with LVH. Conclusions: These results suggest that the shortening of the Pend-Q is a specific finding in Japanese Fabry patients, and the strain pattern without LVH in female patients can be considered Fabry disease. During long-term ERT, prolongation of the QRS duration and QTc can indicate the progression of myocardial damage in male patients with LVH and in female patients with the classical type mutation.